2007
DOI: 10.1590/s0074-02762007005000062
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of Aedes aegypti in the Americas using a mitochondrial gene: evidence of multiple introductions

Abstract: To analyze the genetic relatedness and phylogeographic structure of Aedes aegypti, we collected samples from 36 localities throughout the Americas (Brazil, Peru, Venezuela, Guatemala, US), three from Africa (Guinea, Senegal, Uganda), and three from Asia (Singapore, Cambodia, Tahiti

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
93
3
15

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(131 citation statements)
references
References 31 publications
20
93
3
15
Order By: Relevance
“…Haplotype 3, the most frequent (44.2%), was not detected at all cities surveyed. This haplotype was absent from Maringá, although Bracco et al (2007) had previously found it there. The cities where haplotype H3 was most frequent were Palotina (100%) and Barra do Jacaré (77.7%).…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Haplotype 3, the most frequent (44.2%), was not detected at all cities surveyed. This haplotype was absent from Maringá, although Bracco et al (2007) had previously found it there. The cities where haplotype H3 was most frequent were Palotina (100%) and Barra do Jacaré (77.7%).…”
Section: Discussionmentioning
confidence: 79%
“…aegypti in Paraná. In a previous study, Bracco et al (2007) sequenced the same fragment of the ND4 gene from two specimens from Foz do Iguaçu and three specimens from Maringá. Paduan & Ribolla (2008) employed ten specimens from Londrina.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations